Revitalisasi Strategi Inovasi Ekonomi Bisnis di Era Digital Berkelanjutan untuk Gen Z - Ulya, Millatul (Reinforce: Journal of Sharia Management, 2024)
In the ever-evolving digital era, generation Z has emerged as consumers and workforce with unique characteristics. This study discusses the importance of revitalizing sustainable business economic innovation strategies to meet the needs and preferences of generation Z. This study identifies the challenges and opportunities faced by businesses in adopting digital technology and sustainable practices. Through an analytical approach, this paper explores various innovative strategies that companies can implement to attract and retain generation Z as customers and employees. The results of the study indicate that the integration of technology, sustainability, and social engagement are key factors in creating added value for businesses in the digital era. Thus, companies that are able to adapt and innovate according to the demands of generation Z will have a significant competitive advantage.